The Structural Effect of Electrode Mesh on Hydrogen Evolution Reaction Performance for Alkaline Water Electrolysis - Lee, Hae In; Cho, Hyun-Seok; Kim, MinJoong; Lee, Jae Hun; Lee, ChangSoo; Lee, Sechan; Kim, Sang-Kyung; Kim, Chang-Hee; Yi, Kwang Bok; Cho, Won-Chul (Frontiers in Chemistry, 2021)
Alkaline water electrolysis (AWE) is a mature water electrolysis technology that can produce green hydrogen most economically. This is mainly attributed to the use of Ni-based materials that are easy to process and inexpensive. The nickel-based meshes with various structures such as woven mesh and expanded mesh are widely used as electrode in the AWE due to its common availability and easy fabrication. However, the morphological effect of meshes on HER performance has not been studied. Here a new parameter to determine the structural effect of mesh on HER performance was first proposed. The key factors of the new parameter was found to be the strand width, pore width and the strand surface area. The woven mesh with the ratio of pore width to strand width that converges to 1 showed the lowest the overpotential. The expanded mesh with the higher the structural surface area exhibited the lowest the overpotential. This study will help to choose an optimal structure for the mesh with the hydrogen evolution reaction (HER) electrode